دعوت و تعلیم میں اشارات کا کردارسیرت النبی ﷺ کی روشنی میں: Role of Gesture in invitation and education in light of Seerah - Muhammad Arif Bangash, (Seerat Studies, 2024)
Prophet Muhammad ﷺ is the source of guidance. Following the sayings and actions of the Prophet ﷺ is a guarantee of success in this world and the hereafter. The chain of benefiting from your holy person has been going on for fourteen and a half hundred years and billions of people will continue to benefit from your blessed personality until the Day of Judgment. It is true that every contribution of yours is a model and a beacon for our practical life. These allusions are so effective and of such importance in the narrative that they have become a subject of biographical studies, hence they need to be studied separately. We will discuss in these lines the types of Isharat al-Nabi with examples, and we will try to add something to the topic of Isharat al-Nabi ﷺ through this study. In this article we have presented 40 hadith as samples from which you can know the nature of these signs